The invention of the Creek Nation, 1670-1763 - Hahn, Steven C., 1968- (Indians of the Southeast., 2004)
Drawing on archaeological evidence and utilizing often neglected Spanish source material, The Invention of the Creek Nation, 1670-1763, explores the political history of the Creek Indians of Georgia and Alabama and the emergence of the Creek Nation during the colonial era in the American Southeast. In part a study of Creek foreign relations, this book examines the creation and application of the "neutrality" policy-defined here as the Coweta Resolution of 1718-for which the Creeks have long been famous, in an era marked by the imperial struggle for the American South